2018
DOI: 10.3389/fsurg.2018.00047
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Current Knowledge About Sublay/Retro-Rectus Repair of Incisional Hernias?

Abstract: Introduction: There continues to be very little agreement among experts on the precise treatment strategy for incisional hernias. That is the conclusion drawn from the very limited scientific evidence available on the repair of incisional hernias. The present review now aims to critically assess the data available on the sublay/retro-rectus technique for repair of incisional hernia. Materials and Methods:A systematic search of the literature was performed in May 2018 using Medline, PubMed, and the Cochrane Lib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 72 publications
1
13
0
Order By: Relevance
“…Nonetheless, an Expert Consensus Guided by Systematic Review found that, while the sublay operation should be given preference for incisional hernia repair, the onlay mesh location might be useful in certain settings ( 13 ). Therefore, in this present review the available data on the onlay technique in incisional hernia repair were collated in order to compare this method with the sublay technique ( 38 ). In this analysis, too, it was revealed that the onlay technique was associated with a higher post-operative complication rate, with a mean value of 33.5% and range from 5 to 76%, than the sublay technique, with mean value of 18.6% and range from 8 to 26% ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, an Expert Consensus Guided by Systematic Review found that, while the sublay operation should be given preference for incisional hernia repair, the onlay mesh location might be useful in certain settings ( 13 ). Therefore, in this present review the available data on the onlay technique in incisional hernia repair were collated in order to compare this method with the sublay technique ( 38 ). In this analysis, too, it was revealed that the onlay technique was associated with a higher post-operative complication rate, with a mean value of 33.5% and range from 5 to 76%, than the sublay technique, with mean value of 18.6% and range from 8 to 26% ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in this present review the available data on the onlay technique in incisional hernia repair were collated in order to compare this method with the sublay technique ( 38 ). In this analysis, too, it was revealed that the onlay technique was associated with a higher post-operative complication rate, with a mean value of 33.5% and range from 5 to 76%, than the sublay technique, with mean value of 18.6% and range from 8 to 26% ( 38 ). The mean value for the recurrence rate in the onlay technique was 9.9% with a range from 0 to 32% and, as such, was comparable with the results of the sublay operation with mean value of 13.5% and range from 1.6 to 32% ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of these findings with the outcomes reported in the literature for sublay repair of incisional hernia reveals that in the case of the sublay technique the postoperative complication rates are between 8.0 and 26.0%, with a mean value of 18.6%, and recurrence rates of between 1.6 and 32.0%, with a mean value of 13.5% ( 29 ). Hence, only in respect of the extreme values are the outcomes better for the sublay technique.…”
Section: Discussionmentioning
confidence: 67%
“…Further studies are urgently needed to better ascertain the role of open IPOM with bridging. However, comparison of the literature data on the outcomes of the open IPOM vs. sublay technique did not reveal any essential difference (sublay: mean postoperative complication rate 18.6% (range 8.0–26%), mean recurrence rate 13.5% (range 1.6–32%)] ( 29 ). Only on evaluation of upward-deviating maximum values is a trend toward better outcomes for the sublay technique demonstrated ( 29 ).…”
Section: Resultsmentioning
confidence: 99%
“…But for a defect size greater than 8-10 cm, the recurrence rate rises sharply following laparoscopic IPOM [10][11][12][13][14][15][16]. For the open mesh procedures for treatment of ventral and incisional hernias, systematic reviews and meta-analyses show the best outcomes for the sublay repair [17][18][19][20]. In the Expert Consensus guided by systematic review, the panel agreed that for open elective incisional hernia repair, sublay mesh location is preferred, but open intraperitoneal onlay mesh (IPOM) and onlay mesh may be useful in certain settings [4].…”
Section: Introductionmentioning
confidence: 99%